Character Education and Language - E. Sulyati (International Journal of Science and Society, 2020)
This paper describes the link between educational character and language education. Educational character is an important solution to overcome the moral decline, among young people (especially students). Educational character is closely related to language education, because some of the values of the character contained in the language education. Schools play an important role as a vehicle for character building and reinforce the cultural values of the nation. Language education, including literary, is one vehicle for shaping the character of students. In other words, it has a role in the formation of character. In learning the language and literature, strategies, methods, media, and teaching materials need to be optimized to form the character of students. Yet, language education is not only the duty and responsibility of the language teacher, but the responsibility of all teachers because all the teachers definitely use language. Thus, the most important thing to do is to increase students reading ability which is a key to success.